Improving Consistency of UML Diagrams and Its Implementation Using Reverse Engineering Approach - Vasanthi Kaliappan; Norhayati Mohd Ali (Institute of Advanced Engineering and Science, 2018)
Software development deals with various changes and evolution that cannot be avoided due to the development processes which are vastly incremental and iterative. In Model Driven Engineering, inconsistency between model and its implementation has huge impact on the software development process in terms of added cost, time and effort. The later the inconsistencies are found, it could add more cost to the software project. Thus, this paper aims to describe the development of a tool that could improve the consistency between Unified Modeling Language (UML) design models and its C# implementation using reverse engineering approach. A list of consistency rules is defined to check vertical and horizontal consistencies between structural (class diagram) and behavioral (use case diagram and sequence diagram) UML diagrams against the implemented C# source code. The inconsistencies found between UML diagrams and source code are presented in a textual description and visualized in a tree view structure.